2022
DOI: 10.1101/2022.05.31.494137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial pyruvate metabolism regulates the activation of quiescent adult neural stem cells

Abstract: Cellular metabolism is important for adult neural stem/progenitor cell (NSPC) behavior. However, its role in the transition from quiescence to proliferation is not fully understood. We here show that the mitochondrial pyruvate carrier (MPC) plays a crucial and unexpected part in this process. MPC transports pyruvate into mitochondria, linking cytosolic glycolysis to mitochondrial tricarboxylic acid cycle (TCA) and oxidative phosphorylation (OXPHOS). Despite its metabolic key function, the role of MPC in NSPCs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The important role of neuronal mitochondria in developmental and adult neurogenesis has become evident over the last years (Arra ´zola et al, 2019;Khacho and Slack, 2018;Rangaraju et al, 2019). Mitochondrial metabolism fundamentally regulates developmental and adult neurogenesis and differentiation (Beckervordersandforth, 2017;Lorenz and Prigione, 2017;Petrelli et al, 2022), and mitochondrial structural dynamics of postmitotic neurons have been shown to drive developmental neurogenesis (Iwata et al, 2020), being instrumental for cell fate decisions at the same time (Bhola and Letai, 2016). Mitochondria are also critical for injury-related responses in the developing brain (Hagberg et al, 2014) through induction of programmed cell death (Yamaguchi and Miura, 2015) or morphogenesis of neurons (Kimura and Murakami, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The important role of neuronal mitochondria in developmental and adult neurogenesis has become evident over the last years (Arra ´zola et al, 2019;Khacho and Slack, 2018;Rangaraju et al, 2019). Mitochondrial metabolism fundamentally regulates developmental and adult neurogenesis and differentiation (Beckervordersandforth, 2017;Lorenz and Prigione, 2017;Petrelli et al, 2022), and mitochondrial structural dynamics of postmitotic neurons have been shown to drive developmental neurogenesis (Iwata et al, 2020), being instrumental for cell fate decisions at the same time (Bhola and Letai, 2016). Mitochondria are also critical for injury-related responses in the developing brain (Hagberg et al, 2014) through induction of programmed cell death (Yamaguchi and Miura, 2015) or morphogenesis of neurons (Kimura and Murakami, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, innate NSPC pools are preserved in specific brain regions throughout an individual's lifetime. Petrelli et al [1] . recently reported that inhibiting mitochondrial pyruvate import stimulated NSPCs to transition from a quiescent state to an active state, thereby promoting neurogenesis in both young and middle‐aged mice.…”
Section: Figurementioning
confidence: 99%
“…However, these transcriptional changes do not necessarily translate into proteomic differences ( Wani et al, 2022 ), and more-detailed analyses of metabolic requirements during specific NSC transitions have revealed a more complex picture. For example, deletion of the mitochondrial pyruvate carrier (MPC1), which is involved in the import of the end-product of glycolysis, pyruvate, into the mitochondria promotes both NSC activation from quiescence and differentiation into postmitotic neurons, but does not affect proliferation of activated NSCs itself ( Petrelli et al, 2022 preprint). In contrast, long-term depletion of the mitochondrial transcription factor A (TFAM) mostly affects the self-renewal and survival of intermediate progenitor cells, a highly proliferative transient NSC stage shortly after reactivation ( Beckervordersandforth et al, 2017 ).…”
Section: Oxphos or Glycolysis: Not A Simple Choicementioning
confidence: 99%
“…In contrast, decreased proliferation of hippocampal NSCs has also been observed upon aberrant mitochondrial fragmentation due to mutation of Mfn1 and Mfn2 ( Khacho et al, 2016 ), suggesting roles of these different GTPases beyond mitochondrial fission and/or fusion, or an as yet incomplete understanding of the complex transitions these adult NSCs undergo. It is still unclear, for example, whether the mitochondria of in vivo quiescent NSCs are fragmented and immature, as observed in vitro ( Cai et al, 2021 ; Petrelli et al, 2022 preprint), or whether they have a fused or clustered morphology akin to Drosophila ( Fig. 3 C,E) ( Endow et al, 2019 ).…”
Section: Mitochondrial Morphology Dynamics In Nscsmentioning
confidence: 99%